2014
DOI: 10.1155/2014/961863
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Is Differentially Present in Multiple Sclerosis Courses, Early Evident, and Unrelated to Treatment

Abstract: Background. Oxidative stress is well documented in multiple sclerosis (MS) lesions, but its correspondence at peripheral level is still controversial. Objective. To evaluate peripheral oxidative stress markers in MS patients. Methods. We studied total blood levels of Coenzyme Q10 (CoQ10), oxidized and reduced forms of glutathione, malondialdehyde, reactive oxygen species (ROS), anti-oxidized-low-density lipoproteins (anti-oxLDL) antibodies, and antioxidant power (PAO) in 87 patients with different MS clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 56 publications
2
47
0
Order By: Relevance
“…One of the most consistent differences in gene expression between secondary progressive (SP-MS) patients and healthy controls was enhancement of HIF-1α and its downstream components [58]. In this specific inflammatory condition, the increased effort of HIF-1α and VEGF promoting angiogenesis/arteriogenesis and normalizing oxygen levels to maintain oligodendrocyte and neuron functions could be counterbalanced by other molecules, such as reactive oxygen species (ROS) [173][174][175], nitric oxide intermediates and peroxynitrite (RNS) [176]. These molecules could be responsible for mitochondrial dysfunction [173], distal oligodendropathy [177], apoptotic-like cell death and axonal injury [178].…”
Section: Chronic Hypoperfusion Hypoxia and Angiogenesismentioning
confidence: 99%
“…One of the most consistent differences in gene expression between secondary progressive (SP-MS) patients and healthy controls was enhancement of HIF-1α and its downstream components [58]. In this specific inflammatory condition, the increased effort of HIF-1α and VEGF promoting angiogenesis/arteriogenesis and normalizing oxygen levels to maintain oligodendrocyte and neuron functions could be counterbalanced by other molecules, such as reactive oxygen species (ROS) [173][174][175], nitric oxide intermediates and peroxynitrite (RNS) [176]. These molecules could be responsible for mitochondrial dysfunction [173], distal oligodendropathy [177], apoptotic-like cell death and axonal injury [178].…”
Section: Chronic Hypoperfusion Hypoxia and Angiogenesismentioning
confidence: 99%
“…One study [102] comparing 77 healthy controls to 87 patients with MS, however, reported no significant difference; the MS patients were however in clinical remission. Conversely, another study [103] compared 13 MS patients to 15 controls, and found significantly lower MDA in the MS group.…”
Section: Bloodmentioning
confidence: 98%
“…192 Modification of myelin basic protein (MBP) and glial fibrillary acidic protein (GFAP) triggers lesions in white matter 192 that causes MS. Advanced stage of MS causes demyelination and tissue damage due to oxidative stress are found higher in the patients. 193 Ultra sized cerium oxide nanoparticles declines oxidative stress and alleviates motor deficits in MS brain.…”
Section: Multiple Sclerosismentioning
confidence: 99%